2020
DOI: 10.1016/j.celrep.2020.107730
|View full text |Cite
|
Sign up to set email alerts
|

Mature Retina Compensates Functionally for Partial Loss of Rod Photoreceptors

Abstract: SUMMARY Loss of primary neuronal inputs inevitably strikes every neural circuit. The deafferented circuit could propagate, amplify, or mitigate input loss, thus affecting the circuit’s output. How the deafferented circuit contributes to the effect on the output is poorly understood because of lack of control over loss of and access to circuit elements. Here, we control the timing and degree of rod photoreceptor ablation in mature mouse retina and uncover compensation. Following loss of half of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 36 publications
2
41
0
Order By: Relevance
“…We detected fewer mGluR6 positive puncta, reflecting a decreased number of synapses, in 1-month-old P23H retinas ( Figure 2 ), and on the other hand, rod bipolar cell labeling showed indistinguishable staining patterns between P23H and control retinas ( Figure 1—figure supplement 1 ). In line with this, ablation of ~50% of rods in a WT adult mouse retina, phenotypically mimicking the situation in young adult P23H mice including compensation of the ERG b-wave amplitude, did not lead to morphological synaptic changes in the study by Care et al, 2020 . Our RNA-seq data show upregulations in a number of mRNAs of ion channels and G protein-coupled receptors, such as the Trpm1 cation channel crucial for ON bipolar cell depolarization as well as glutamatergic receptors that could contribute either to the strengthening of individual rod-rod bipolar cell synapses or increased excitability of the rod bipolar cells ( Figure 3—figure supplements 3 – 5 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We detected fewer mGluR6 positive puncta, reflecting a decreased number of synapses, in 1-month-old P23H retinas ( Figure 2 ), and on the other hand, rod bipolar cell labeling showed indistinguishable staining patterns between P23H and control retinas ( Figure 1—figure supplement 1 ). In line with this, ablation of ~50% of rods in a WT adult mouse retina, phenotypically mimicking the situation in young adult P23H mice including compensation of the ERG b-wave amplitude, did not lead to morphological synaptic changes in the study by Care et al, 2020 . Our RNA-seq data show upregulations in a number of mRNAs of ion channels and G protein-coupled receptors, such as the Trpm1 cation channel crucial for ON bipolar cell depolarization as well as glutamatergic receptors that could contribute either to the strengthening of individual rod-rod bipolar cell synapses or increased excitability of the rod bipolar cells ( Figure 3—figure supplements 3 – 5 ).…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies using the specific deletion of ~50–90% of rods, cones or rod bipolar cells during development or in mature mice have revealed homeostatic mechanisms associated with the maintenance of normal retinal output and vision ( Care et al, 2020 ; Care et al, 2019 ; Johnson et al, 2017 ; Shen et al, 2020 ; Tien et al, 2017 ). Here we used a P23H knock-in mouse model of RP that recapitulates the human disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rod/cone degeneration does lead to plastic changes in the retina [38,39]. For example, rod to rod bipolar cell signaling is potentiated in rod photoreceptor degeneration, preserving voltage output and scotopic vision [40,41]. Although speculative, it seems likely that the negative masking and PLR phenotypes, in part, reflect plastic changes in retinal cells and circuits.…”
Section: Plos Onementioning
confidence: 99%
“…These rod or cone bipolar dendrites may extend their arbors and form new synapses to compensate for a reduced number of photoreceptor cells (21). A recent study also reported functional compensation in the retina after ablation of 50% of rods, without any observable anatomical changes in the bipolar cells (22). We believe these homeostatic mechanisms may have also contributed to rescuing photopic ERG in the entrained mice in spite of a significant reduction in cone photoreceptor numbers.…”
Section: Discussionmentioning
confidence: 69%